ผลของการใช้แนวคิดสะตีมศึกษาในวิชาชีววิทยาที่มีต่อความคิดสร้างสรรค์ทางวิทยาศาสตร์ และผลสัมฤทธิ์ทางการเรียนของนักเรียนชั้นมัธยมศึกษาปีที่ 4 - อินทวิมลศรี, สมรัก; แก้วดี, สกลรัชต์; ภัทรดิลกรัตน์, สิทธิพร (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were to: (1) investigate the level of students’ scientific creativity after learning biology through the STEAM Education approach, (2) compare students’ scientific creativity before and after learning biology through the STEAM Education approach, and (3) determine the level of students’ learning achievements in biology after learning through the STEAM Education approach. The target group was tenth grade students in the academic year 2016 from a special large secondary school in Bangkok. The design of this pre-experimental research was a one group pretest-posttest design. The students’ scientific creativity was evaluated before and after instruction, while students’ achievement in biology was only evaluated after instruction. The research instruments were: (1) the scientific creativity test (2) product design and product evaluation forms for scientific creativity performance assessment, and (3) an achievement test in biology. The collected data were analyzed by mean, percentage mean, standard deviation, and t-test.The research findings were summarized as follows: (1) the scientific creativity of these students was rated at the good level and above, (2) there was no significant difference in the students’ scientific creativity between before and after the instruction, and (3) students’ achievement in biology was rated at the medium level.